Think again : why good leaders make bad decisions and how to keep it from happening to you - Finkelstein, Sydney. (Harvard Business Press, 2008)
Packed with compelling stories from various industries and disciplines, 'Think Again' offers illuminating insights on the potential flaws in how we all make decisions.